A new species of Yunnanilus (Cypriniformes: Nemacheilidae) from upper Pearl River, Yunnan, China - He, Yun-Rui; Li, Xue-Rong; Che, Xing-Jin; Yang, Xiao-Jun; Wang, Ji-Shan; Wang, Mo (Zootaxa, 2024)
A new species (Cypriniformes: Nemacheilidae) Yunnanilus yangi sp. nov. was described from Upper Pearl River (Nanpan Jiang) in Mile County, Honghe Hani and Yi ethnic Autonomous Prefecture, Yunnan Province, China. Yunnanilus yangi sp. nov. can be distinguished from other species within the genus by the following characteristics: (1) upper lip with median incision; (2) upper jaw without processus dentiformis; (3) dorsal-fin origin closer to snout tip base than to caudal-fin base; (4) pelvic-fin rays i, 6-7; (5) branched caudal-fin rays 16 (vs. 14-16). According to morphological comparison, Yunnanilus yangi sp. nov. can be distinguished clearly from all the other species in the Yunnanilus. In addition to the morphological characteristics, phylogenetic analysis of the mitochondrial cytochrome b further confirmed that Yunnanilus yangi sp. nov. is a member of Yunnanilus. Furthermore, the least genetic distance between Yunnanilus yangi sp. nov. and other species of Yunnanilus in cytochrome b gene reached 6.33%.